Comparison of the Effects of Glycyrrhiza Glabra Vaginal Cream and Clotrimazole on the Symptoms of Fungal Vulvovaginitis - N Dodangeh; M Kheirkhah; J Abolghasemi; F Mojab; F Farshad (Iran University of Medical Sciences, 2019)
Background & Aims: Candidiasis accounts for 50-90% of vaginal infections in women. Resistance to azole drugs has prompted research into new drugs for the treatment of vaginal infections. The present study aimed to compare the effects of Glycyrrhiza Glabra vaginal cream and clotrimazole on the symptoms of fungal vulvovaginitis. Materials & Methods: This triple-blind clinical trial was conducted on 60 women with candida vaginitis. The inclusion criteria were the presence of two symptoms of fungal vulvovaginitis (itching, burning, discharge, dyspareunia, and dysuria) and positive vaginal smear. After obtaining informed consent, eligible subjects chose the cards A or B and were assigned to each study group. The patients used an applicator containing clotrimazole or Glycyrrhiza Glabra vaginal cream every night, which were prepared in identical tubes (50 mg) and labeled A or B by a pharmacist. Data were collected using demographic and fertility forms, a checklist of clinical observations, and a record of the results of vaginal smear. After completing the treatment period for seven days, the subjects referred to the gynecological clinic again for examination and vaginal smears. Data analysis was performed in SPSS version 16 using Chi-square, McNemar's test, and generalized estimating equation. Results: The results of vaginal smear and improved symptoms of vulvovaginitis (discharge, dyspareunia, irritation, and irritation) were similar in clotrimazole and Glycyrrhiza Glabra groups, while the improvement of the symptoms of itching and burning was more significant in the clotrimazole group compared to the Glycyrrhiza glabra group. Conclusion: According to the results, Glycyrrhiza Glabra vaginal cream could be used as an adjunct therapy to major treatments in the women who are willing to use herbal medication. Therefore, it should be recommended to midwives and gynecologists.